Raw material formula of luminous waterstone - YANG HUI; FAN XIANPING; WANG HAIFENG; QIAN XIAO; SHEN ZHICHENG (2016)
The invention belongs to the field of building materials, and aims to provide a raw material formula of a luminous waterstone. The raw material formula comprises the following components in parts by weight: 100 parts of metakaolin, 10 to 20 parts of an alkali-activator, 80 to 120 parts of an inorganic aggregate, 5 to 20 parts of luminous stones and 30 to 50 parts of water, wherein the alkali-activator is NaOH or Na2O nSiO2, and n is equal to 1.0 to 2.0. With a geopolymer serving as a gel material, the raw material formula is low in energy consumption and low in environmental pollution; the prepared luminous waterstone is high in breaking strength and low in water absorption rate, and can be widely applied. 本发明属于建筑材料领域，旨在提供种夜光水磨石的原料配方。包括下述按重量比计算的各组分：偏高岭土100份、碱激发剂10～20份、无机骨料80～120份、夜光石5～20份、水30～50份，所述碱激发剂为NaOH或Na2O·nSiO2，n＝1.0～2.0。本发明以地聚合物为胶凝材料，能耗少、环境污染小；制备所得的水磨石抗折强度高，吸水率低，应用领域广泛。